Analysis of Biology Textbook Class X 2013 Curriculum Based on Science Literacy Category Integrated Islamic Values in the Concept of Environmental Change - Amalia Mahmudah; Wahidin Wahidin; Ria Yulia Gloria (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2021)
Scientific literacy that integrates Islamic values in books helps students understand science and apply it in daily life. The integration of Islam aims to build students' character to become cognitively intelligent and intelligent in attitude and behavior. This study describes scientific literacy that integrates Islamic values and the level of scientific literacy that integrates Islamic values in textbooks. The research design uses a qualitative approach with content analysis methods. Research data collection techniques using observation sheets. The results showed that the biology textbooks for class X SMA from the publishers of Erlangga, Grafindo, and Tiga Serangkai contained scientific literacy that was integrated with Islamic values.